Sustained collective action for integrated pest management - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Every year, crop and animal pests deprive farmers of significant parts of their production. It is estimated that 10-40 percent of the world's gross agricultural production is destroyed by agricultural pests. These pests include a huge variety of different organisms, not only insects, mites, worms, rodents, and birds, but also, in a broader sense, all organisms such as weeds, fungi, bacteria, and viruses. The variety of pests and their interactions with other ecosystem conditions make pest problems very diverse and often complex, so solutions to single pest problems must vary substantially. Some pests can be controlled by individual farmers; others are amenable to public programs like aerial spraying. Many pest management approaches, however, call for neighbors to work together. Collective action is particularly important for reducing pesticides in agriculture.